PERAN KEPRIBADIAN DALAM MEMBENTUK KARAKTER KEPEMIMPINAN TRANSFORMASIONAL DI KALANGAN GENERASI MUDA - Sadrakh Sugiono; Rina Ria Sitohang (Bethel Press, 2023)
This study aims to explore the role of personality in shaping transformational leadership character among young leaders. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving young leaders aged 18–30 engaged in youth organizations. Thematic analysis revealed that extraversion, openness to experience, conscientiousness, and agreeableness support transformational behaviors such as inspirational motivation, intellectual stimulation, and individualized consideration, while neuroticism hinders the consistency of such behaviors. The findings highlight the importance of considering dispositional factors in developing transformational leadership to ensure long-term character formation rather than short-term behavioral change. The emerging adulthood phase is identified as a strategic period for interventions in values, character, and readiness to face socio-digital challenges. These insights imply the need for personality-based leadership development strategies that integrate self-regulation and digital literacy for young leaders